On-Demand PrEP: Clinical Report of Pharmaceutical Care in HIV Pre-Exposure Prophylaxis - Ribeiro, André Luiz; Siqueira, Luane da Silva Oliveira; Dewulf, Nathalie de Lourdes Souza; Lopes, Angela Ferreira (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: Pre-Exposure Prophylaxis (PrEP) for HIV involves the combined use of antiretrovirals for individuals frequently exposed to HIV. Initially implemented in Brazil in 2018 with a daily dosing regimen of one pill, on-demand usage was recently (2022) incorporated into routine practice. Aim: To report the experience of providing pharmaceutical care to an on-demand PrEP patient in an outpatient pharmacy within Brazil's Unified Health System. Outlining: This experience report details of pharmaceutical care that included reception of the patient, conducting anamnesis, legally and technically prescription evaluation, dispensing PrEP with verbal guidance on potential adverse events related to pharmacotherapy, and scheduling a return visit to the service. Results: The patient was initially prescribed a daily regimen of PrEP. During the first return consultation, 30 days after starting PrEP, the patient reported adverse effects related to the gastrointestinal tract, leading to the recommendation of an on-demand PrEP regimen. Implications: As of the last pharmaceutical consultation (June 21, 2022), the patient maintained a negative HIV serology, was accustomed to the newly prescribed dosage, and reported reduced gastric discomfort associated with the use of on-demand PrEP. This facilitated adherence to pharmacotherapy and improved the preventive efficacy against HIV infection.